The 1931 Spanish constitutional debate on freedom of conscience: a discussion about the relations between Church and State - Bellido, Francisco J. (EUNOMÍA. Revista en Cultura de la Legalidad, 2017)
This study examines the Spanish parliamentary debate of 1931, in the framework of the debate on the new Constitution, about freedom of conscience through the relations between Church and State outlined by the different political parties. It defends that the debate on freedom of conscience deals mainly with the role of both institutions in the new constituent order. The first part of this article shows parliamentary sessions on freedom of conscience that took place in September 1931. In the second part some clarifications regarding the political vocabulary used by the constituents are introduced. It pays attention to the use of common political: secularisation, autonomy, liberty and State. In the third part the arguments held by the representative during October 1931 are examined. Finally, it summarises the arguments supporting the article’s hypothesis.